Cardiac Arrest during Cesarean Section – A Case Report and Review of the Differential Diagnosis - Lukac, Stefan; Mayer, Sebastian; Mühlen, Kathrin; Flock, Felix (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Aim According to the World Health Organization, approximately 810 pregnant women die every day as a consequence of peripartum complications. A large proportion of deaths happen in developing countries. Peripartum cardiac arrest is a rare event that must be treated immediately. It is important to consider the differential diagnoses in order to save lives.Methods In this review, we discuss a differential diagnosis of cardiac arrest according to the BEAU-CHOPS scheme of the American Heart Association in the relation to the case report of our 40-year-old G5/P3 patient who went into cardiac arrest during cesarean delivery.Results Typical differentials for cardiac arrest during labor are bleeding, embolism, anesthetic complications, cardiovascular diseases, eclampsia, and sepsis. All of them were considered and ruled out in this patient. In the end, we suspect that physiological cardio-inhibitory reflexes triggered by sudden profound hypovolemia after placental separation along with the patientʼs risk factors, especially obesity and maternal age, and the administration of spinal anesthesia all potentially contributed to the cardiac arrest.Conclusions This review highlights that the cardiac arrest during labor can be triggered by the multifactorial etiology, but firstly the typical differential diagnosis needs to be excluded.
Keywords: asystole; cardiac arrest; caesarean section; labor